MONOFRACTAL AND MULTIFRACTAL ANALYSIS IN SHORT - TERM TIME DYNAMICS OF ULF GEOMAGNETIC FIELD MEASURED IN CRETE, GREECE - Vallianatos, F.; Makris, J. P.; Saltas, V.; Telesca, L.; Lapenna, V. (Bulletin of the Geological Society of Greece, 2004)
In this work, a monofractal and multifractal characterization of the short-term time dynamical fluctuations of the ultra low frequency (ULF) geomagnetic field, measured by one station installed in Creete, Greece, has been carried out. Time scale properties of the three ULF geomagnetic components, two horizontal (x, y) and one vertical (z) have been analyzed through the power spectral density, Higuchi method and Hurst R/S analysis. Results point out the presence of fractal features expressing long-range time correlation with scaling coefficients, which are the clue of persistent mechanism. Using a set of multifractal parameters, defined from the shape of the multifractal spectrum, it has been observed that the degree of multifractality, that characterizes the original signals, is "weaker" if compared to the residual signals, obtained from the original ones after removing the four observed periodicities (24-, 12-, 8- and 6-h periodicties). Furthermore the horizontal χ and y components have revealed to be less multifractal than the vertical z-component.